A graphitized cathode carbon block assembly and its preparation method and application
By adopting an improved graphitized cathode carbon block group in the aluminum electrolytic cell, the problems of increased cathode voltage and electricity consumption and steel rod leakage are solved, and significant energy saving and corrosion resistance are achieved, and the service life of the electrolytic cell is extended.
Patent Information
- Application Number
- CN202411991008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
When the existing graphitized cathode carbon block set is run in an aluminum electrolytic cell, it is easy to cause the cathode voltage and electricity consumption to increase, and leakage occurs at the steel rod, which affects the normal operation and service life of the electrolytic cell.
A graphitized cathode carbon block group is adopted, including graphitized carbon blocks and steel rods. A steel rod paste layer is provided in the middle of the lower end face of the carbon block, and grooves are provided at both ends. A ceramic fiber blanket layer and a phosphorus pig iron casting layer are arranged in the grooves. The steel rod extension wrapping layer is made of a mixture of water glass and SiC ramming materials, and an anti-seepage casting material layer and anchors are provided on both sides of the lower end of the steel rod.
It significantly reduces the furnace bottom pressure drop of the aluminum electrolytic cell, has obvious energy saving effect, improves the anti-sodium corrosion performance, extends the service life of the cathode structure, and ensures the stable operation and safety of the electrolytic cell.
Smart Images

Figure CN119776910A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum electrolysis, and in particular to a graphitized cathode carbon block group and a preparation method and application thereof. Background Art
[0002] The cathode carbon block group is an important component of the aluminum electrolytic cell lining. During the production process, the performance of the cathode carbon block group has a significant impact on the power consumption and cell life of the electrolytic cell. The cathode carbon block group includes cathode carbon blocks and steel rods. The cathode carbon blocks are mainly divided into anthracite blocks, graphite carbon blocks and graphitized carbon blocks. Graphite carbon blocks are made by roasting graphite fragments instead of part of the electrocalcined anthracite. Graphite carbon blocks are distinguished according to the nominal proportion of artificial graphite in its dry material formula of 10%, 30%, 50%, and 100%. Graphitized cathode carbon blocks are made by mixing petroleum coke and asphalt, roasting them, and then graphitizing them. Compared with graphite carbon blocks, graphitized carbon blocks have good thermal conductivity and electrical conductivity and can withstand higher currents. A steel rod is set at the bottom of the graphitized cathode carbon block. One end of the steel rod is exposed from the end of the cathode carbon block and can be extended out of the aluminum electrolytic cell to connect with the cathode busbar to form the cathode circuit of the aluminum electrolytic cell. The graphitized cathode carbon block and steel rod are usually assembled by carbon paste. The pressure drop of the cathode carbon block group assembled in this way increases significantly after the electrolytic cell is started. The main reason is that under the action of electrocapillary, the electrolyte penetrates into the cathode carbon block, and the electrolyte reacts with metallic sodium at the steel-carbon interface to form sodium fluoride and aluminum. The aluminum reacts with the steel rod to form an aluminum-iron alloy. The deposition of sodium fluoride and the formation of aluminum-iron alloy will lead to the formation of a ring-shaped structure between steel and carbon. The sodium fluoride crystals in the ring-shaped structure form an electrical insulation layer on the outer surface of the steel rod, which will inevitably hinder the current from passing through the interface, resulting in an increase in cathode voltage and power consumption. In addition, the high thermal conductivity of the graphitized carbon block easily leads to the isotherm moving down during the operation of the electrolytic cell, causing overheating at the bottom of the electrolytic cell and the steel rod, which in turn leads to electrolyte leakage at the steel rod, affecting the normal operation of the electrolytic cell and shortening the service life of the electrolytic cell. Summary of the invention
[0003] The invention provides a graphitized cathode carbon block and a preparation method thereof, which can solve the problems of increased cathode voltage and power consumption; leakage easily occurs at the steel rod, affecting the normal operation of the electrolytic cell and shortening the service life of the electrolytic cell.
[0004] This application provides the following technical solutions:
[0005] A graphitized cathode carbon block group comprises a cathode carbon block and a steel rod. The cathode carbon block is a graphitized carbon block. A steel rod paste layer is provided in the middle of the lower end surface of the cathode carbon block. Grooves are provided at both ends of the lower end surface of the cathode carbon block. Steel rods are arranged in the grooves. A ceramic fiber blanket layer is provided between the steel rod and the steel rod paste layer. One end of the steel rod extends from the end of the cathode carbon block to the outside. A wrapping layer is provided on the extension section of the steel rod extending out of the cathode carbon block. The material of the wrapping layer is a mixture of water glass and SiC ramming material. A phosphorus pig iron casting layer is provided between the steel rod and the inner side of the cathode carbon block. A ramming material layer is provided between the steel rod and the end of the cathode carbon block. The lower end of the steel rod extends downward from the lower end surface of the cathode carbon block. Anti-seepage casting material layers are provided on both sides of the lower end of the steel rod. A plurality of anchors are symmetrically provided on both sides of the lower end of the steel rod. Plastic pipes are sleeved on the anchors. The anchors are located in the anti-seepage casting material layer.
[0006] A method for preparing a graphitized cathode carbon block assembly comprises the following steps:
[0007] S1, mixing the raw materials, calcining them at 1000-1200° C. for 10-15 hours, and after cooling, transferring them to a graphitization furnace for graphitization at 2500-2700° C. for 10-15 hours. After graphitization, forming them with a vibration forming machine, opening grooves, and obtaining a graphitized cathode carbon block;
[0008] S2, sand wash the surface of the steel rod to remove rust from the steel rod, revealing a silver-grey metallic luster;
[0009] S3, installing the steel rod into the groove of the cathode carbon block, heating the steel rod and the cathode carbon block, and quickly pouring the phosphorus pig iron molten liquid into the groove gap between the steel rod and the cathode carbon block to form a phosphorus pig iron pouring layer;
[0010] S4. After the phosphorus pig iron casting is completed and cooled, the end of the cathode carbon block is filled with ramming material, and the three sides of the steel rod extension section are coated with a mixture of water glass and SiC ramming material to form a wrapping layer;
[0011] S5. Anchors are welded on both sides of the steel rod, the anchors are wrapped with plastic tubes, and an anti-seepage castable is poured to form an anti-seepage castable layer;
[0012] S6. A ceramic fiber blanket is arranged in the middle of the cathode carbon block near the steel rod, and the middle space is filled with paste to form a steel rod lake layer.
[0013] A graphitized cathode structure for an aluminum electrolytic cell using a graphitized cathode carbon block group.
[0014] Beneficial effects: The bottom pressure drop of the aluminum electrolytic cell using the graphitized cathode carbon block group is significantly reduced, and the energy-saving effect is obvious; the graphitized cathode carbon block group has better resistance to sodium corrosion and can extend the service life of the cathode structure of the aluminum electrolytic cell; the performance of the graphitized cathode carbon block is uniform, and the probability of local early damage after being put into electrolytic operation is very small, which is conducive to the smooth operation of the overhaul cell; the graphitized cathode carbon block group has stable properties, and the cathode current distribution is more uniform after being put into electrolytic operation, which is conducive to the stable operation of the electrolytic cell.
[0015] The graphitized cathode carbon block has low resistivity (the resistivity at 1000°C is below 10μΩ·m) and high thermal conductivity (the thermal conductivity at 1000°C is above 50W / m·K). The steel rod is changed from a traditional double steel rod to a single steel rod, which increases the contact area between the steel rod and the cathode carbon block. Therefore, the heat generation at the steel rod is significantly reduced and the heat dissipation is greatly increased. The heat at the steel rod in the aluminum electrolytic cell can be dissipated outwardly through the steel rod extension section, and it is also convenient to cool the inner side of the aluminum electrolytic cell by cooling the steel rod extension section, reducing the difference in thermal shrinkage between the graphitized cathode carbon block and the cathode paste, eliminating or reducing the probability of cracks between carbon seams, preventing leakage at the steel rod, and ensuring the safety and normal operation of the electrolytic cell.
[0016] The graphitized electrolytic cell includes a graphitized cathode carbon block group, an electrolytic cell lining structure and masonry materials. The graphitized cathode carbon block group is formed by assembling the graphitized cathode carbon block and the cathode steel rod by the phosphorus pig iron casting method. The graphitized cathode carbon block group is masonry-made with high-strength ceramic fiberboard and vermiculite insulation bricks with better thermal insulation performance, so that the electrolytic cell can achieve a good thermal balance state. Due to the graphitized carbon block and phosphorus pig iron steel rod casting technology, the conductivity of the cathode carbon block is improved, which can maintain a low cathode voltage drop and a stable magnetic fluid state, greatly improve the economic and technical indicators, and extend the life of the electrolytic cell.
[0017] Furthermore, the weight ratio of water glass to SiC ramming material in the wrapping layer is 1-1.5:2-4, and the thickness of the wrapping layer is 0.5-1.5 mm.
[0018] Beneficial effects: Water glass can form a dense protective film to isolate the electrolyte from direct contact with the steel rod to prevent corrosion. It can also fill tiny gaps, provide good sealing, and prevent electrolyte leakage. SiC ramming material itself has strong chemical stability and can maintain performance in a strong corrosive environment. It also has extremely high thermal conductivity, which helps to quickly conduct heat and maintain a stable temperature distribution. The weight ratio of water glass and SiC ramming material is in the range of 1-1.5:2-4, so that the wrapping layer has high chemical stability to prevent corrosion, and good sealing, which effectively prevents electrolyte leakage. The thickness of the wrapping layer is 0.5-1.5mm, which can ensure its chemical properties while reducing material costs.
[0019] Furthermore, the steel rod is a rectangular structure, and the width of the steel rod is greater than the thickness of the steel rod.
[0020] Beneficial effect: The width of the rectangular steel bar is greater than its thickness, which can increase the contact area with the cathode carbon block, thereby improving the electrical conductivity and heat conduction efficiency. Compared with the "thin and tall" steel bar in the prior art, that is, the width of the steel bar is less than the thickness of the steel bar, it can effectively improve the success rate of phosphorus pig iron casting and reduce the stress of the graphitized cathode carbon block group.
[0021] Furthermore, the thickness of the graphitized cathode carbon block group is above 480 mm.
[0022] Beneficial effects: In the prior art, the height of the cathode carbon block group is generally around 460 mm. Increasing the height of the graphitized cathode carbon block group can enhance wear resistance, slow down the consumption rate of the carbon blocks, and increase the service life of the graphitized cathode carbon block group. It can ensure that the carbon blocks can be used for 7-8 years under wear and tear, thereby extending the service life.
[0023] Further, the raw materials of step S1 include electroforged anthracite, petroleum coke, asphalt, NbN additive and H3BO3 additive.
[0024] Beneficial effects: The cathode carbon block prepared using the above principle has high electrical conductivity and thermal conductivity, low ash content, can effectively reduce the impurity content of the cathode carbon block during use, and has good oxidation resistance.
[0025] Furthermore, the anchor in step S6 is wrapped with a plastic tube having a thickness of 1.0 to 1.5 mm.
[0026] Beneficial effects: The 1.0-1.5 mm thick plastic tube can effectively buffer the expansion stress of the anchor nail after heating, and can also protect the anchor from moisture and water loss of the castable, thereby extending the service life of the anchor.
[0027] Furthermore, the graphitized cathode structure of the aluminum electrolytic cell includes, from bottom to top, a cell shell, an insulation layer, an anti-seepage layer and a graphitized cathode carbon block group layer; the insulation layer includes, from bottom to top, a brucite composite insulation brick layer, a hard calcium silicate insulation brick layer, a high-strength ceramic fiber board layer and a ceramic vermiculite insulation board layer; the anti-seepage layer includes, from bottom to top, a steel plate and a dry anti-seepage material layer; the graphitized cathode carbon block group layer includes a plurality of graphitized cathode carbon block groups distributed in parallel, and the periphery of the graphitized cathode carbon block group layer is provided with, from the inside to the outside, a cathode paste layer, an anti-seepage casting material layer, a vermiculite insulation brick layer and a hard calcium silicate insulation brick layer.
[0028] Beneficial effects: Through the combined use of multiple layers of thermal insulation materials, the temperature distribution in the electrolytic cell is effectively controlled, the risk of local overheating is reduced, and the thermal balance of the cathode structure of the aluminum electrolytic cell is ensured. Electrolyte leakage is prevented, the safe operation of the electrolytic cell is ensured, and the risk of environmental pollution is reduced.
[0029] Furthermore, the wrapping layer of the steel rod extension section corresponds to the cathode paste layer and the anti-seepage casting material layer.
[0030] Beneficial effects: The wrapping layer can effectively isolate the steel rod from the external environment, prevent electrolyte leakage, and ensure the sealing of the connection parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a front view and a partial cross-sectional view of a graphitized cathode carbon block assembly of the present invention.
[0032] Figure 2 It is a top view and a partial cross-sectional view of a graphitized cathode carbon block assembly of the present invention.
[0033] Figure 3 for Figure 1 AA section view.
[0034] Figure 4 for Figure 2 BB section view.
[0035] Figure 5 It is a cross-sectional view of the graphitized cathode structure of the aluminum electrolytic cell of the present invention.
[0036] The marks in the drawings of the specification include: cathode carbon block 1, steel rod 2, steel rod paste layer 3, phosphorus pig iron casting layer 4, ramming material layer 5, ceramic fiber blanket layer 6, anchor 7, anti-seepage casting material layer 8, wrapping layer 9, brucite composite insulation brick layer 10, hard calcium silicate insulation brick layer 11, high-strength ceramic fiber board layer 12, ceramic vermiculite insulation board layer 13, steel plate 14, dry anti-seepage material layer 15, cathode paste layer 16, anti-seepage casting material layer 17, vermiculite insulation brick layer 18, side block 19, special-shaped block 20. DETAILED DESCRIPTION
[0037] The following is further described in detail through specific implementation methods:
[0038] like Figures 1 to 5 As shown, a graphitized cathode carbon block group includes a cathode carbon block 1 and a steel rod 2. The cathode carbon block 1 is a graphitized carbon block. A steel rod paste layer 3 is provided in the middle of the lower end surface of the cathode carbon block 1. Two dovetail-shaped grooves for installing the steel rod 2 are provided at both ends of the lower end surface of the cathode carbon block 1. The two grooves are symmetrically arranged on both sides of the steel rod paste layer 3. The steel rod paste layer 3 is made of high-graphite carbon material. The outer periphery of the cathode carbon block 1 is provided with a plurality of grooves, including a first groove and a second groove. The extension direction of the first groove is the same as the extension direction of the groove. The first groove is evenly distributed on the outer walls on both sides of the cathode carbon block 1. The cross section of the first groove is a trapezoidal structure; the extension direction of the second groove is perpendicular to the extension direction of the groove. The second groove is located on the outer walls at both ends of the cathode carbon block 1 and is located above the groove. The cross section of the second groove is a triangular structure. The spacing between the first grooves is greater than the spacing between the second grooves.
[0039] Steel rods 2 are symmetrically arranged in two grooves on the lower end surface of the cathode carbon block 1. One end of the steel rod 2 is close to the steel rod paste layer 3, and a ceramic fiber blanket layer 6 is arranged between the steel rod 2 and the steel rod paste layer 3. The other end of the steel rod 2 extends from the end of the cathode carbon block 1 to the outside. The steel rod 2 extends out of the cathode carbon block 1. The extension section of 120mm is provided with a wrapping layer 9 on three sides. The bottom surface of the steel rod 2 is not brushed with the wrapping layer 9. The thickness of the wrapping layer 9 is 0.5-1.5mm. The material of the wrapping layer 9 is a mixture of water glass and SiC ramming material. The weight ratio of water glass to SiC ramming material is 1.35:2.5. A phosphorus pig iron casting layer 4 is arranged between the steel rod 2 and the inner side of the cathode carbon block 1 close to the ceramic fiber blanket layer 6, and a ramming material layer 5 is arranged between the steel rod 2 and the end of the cathode carbon block 1. The lower end of the steel rod 2 extends downward from the lower end surface of the cathode carbon block 1. A plurality of anchors 7 are symmetrically arranged on both sides of the lower end of the steel rod 2, and a 1.0-1.5mm thick plastic tube is sleeved on the anchor 7. An anti-seepage castable material layer 8 is provided on both sides of the lower end of the steel rod 2 , and the anchor 7 is located in the middle of the anti-seepage castable material layer 8 .
[0040] Specifically, the total thickness D of the graphitized cathode carbon block group is above 480 mm, and the size of the cathode carbon block 1 is 520 mm×430 mm×3390 mm (width×thickness×length). The two side walls of the dovetail groove are symmetrically provided with inwardly extending protrusions, the groove depth (thickness) of the groove is 145 mm, the distance (width) between the two side walls is 260 mm, the minimum distance between the protrusions on the two side walls is 250 mm, and the length of the groove is 1590 mm. The size of the steel rod 2 is 220 mm×180 mm×2045 mm (width×thickness×length), the thickness of the anti-seepage castable layer 8 on both sides of the steel rod 2 is 50 mm, and the thickness of the phosphorus pig iron casting layer 4 is above 15 mm. The size of the ceramic fiber blanket layer 6 is 265 mm×195 mm×30 mm (width×thickness×length).
[0041] A method for preparing a graphitized cathode carbon block assembly:
[0042] S1. The raw materials include electroforged anthracite, petroleum coke, asphalt, NbN additive and H3BO3 additive. The electroforged anthracite, petroleum coke, asphalt, NbN additive and H3BO3 additive are mixed in a mass ratio of 20-25:45-50:10-12:8-10:8-10, the mixing temperature is 160-200°C, and the mixture is calcined at 1000-1200°C for 10-15h. After cooling, the mixture is transferred to a graphitization furnace and graphitized at 2500-2700°C for 10-15h. After graphitization, the mixture is formed by a vibration forming machine and grooves are opened to obtain a graphitized cathode carbon block 1. The density of the graphitized cathode carbon block 1 is 1.62g / cm 3 above.
[0043] S2. Sand wash the surface of the steel rod 2 to remove rust from the steel rod 2, revealing a silver-grey metallic luster.
[0044] S3. Wrap aluminum silicate round braid around both ends of the steel rod 2, install the steel rod 2 into the groove of the cathode carbon block 1, heat the steel rod 2 and the cathode carbon block 1 to 500-650°C, and quickly pour the phosphorus pig iron molten liquid with a temperature of 1400-1450°C into the groove gap between the steel rod 2 and the cathode carbon block 1 to form a phosphorus pig iron pouring layer 4.
[0045] S4. After the phosphorus pig iron casting is completed and cooled, the aluminum silicate round braided rope at the end of the cathode carbon block 1 is removed, and the corresponding position is filled with ramming material. A mixture of water glass and SiC ramming material is applied on three sides of the steel rod extension section to form a wrapping layer 9, and the thickness of the wrapping layer 9 is 0.5-1.5 mm.
[0046] S5. Anchor pieces 7 are welded on both sides of the steel rod 2. The anchor pieces 7 are wrapped with 1.0-1.5 mm thick plastic tubes. An anti-seepage casting material is poured to form an anti-seepage casting material layer 8.
[0047] S6. A ceramic fiber blanket is arranged in the middle of the cathode carbon block 1 near the steel rod 2, and the middle space is filled with paste to form a steel rod lake layer 3.
[0048] A graphitized cathode structure of an aluminum electrolytic cell using a graphitized cathode carbon block group includes, from bottom to top, a cell shell, an insulation layer, an anti-seepage layer, and a graphitized cathode carbon block group layer. The insulation layer includes, from bottom to top, a brucite composite insulation brick layer 10, a xonotlite insulation brick layer 11, a high-strength ceramic fiber board layer 12, and a ceramic vermiculite insulation board layer 13. The anti-seepage layer includes, from bottom to top, a steel plate 14 and a dry anti-seepage material layer 15. The graphitized cathode carbon block group layer includes a plurality of graphitized cathode carbon block groups arranged in parallel, and the periphery of the graphitized cathode carbon block group layer is provided with, from inside to outside, a cathode paste layer 16, an anti-seepage casting material layer 17, a vermiculite insulation brick layer 18, and a xonotlite insulation brick layer 11. The two steel bars 2 of the graphitized cathode carbon block group extend from the two side walls of the tank shell to the outside and are connected to the cathode busbar. The gap between two adjacent graphitized cathode carbon block groups is 30-35 mm. The gap and periphery between the graphitized cathode carbon block groups are provided with cathode paste. Vermiculite insulation bricks are first laid between the steel bars of the two adjacent graphitized cathode carbon block groups and then anti-seepage casting materials are poured. Hard calcium silicate insulation bricks are arranged outside the vermiculite insulation bricks. The upper surface of the anti-seepage casting material around the cathode carbon block is smoothed, and a side block 19 and a special-shaped block 20 are arranged above the anti-seepage casting material. The special-shaped block 20 is made of carbon material, and the side block 19 is a silicon carbonitride brick or a silicon carbonitride composite brick embedded with a ceramic fiber board. The silicon carbonitride composite brick embedded with a ceramic fiber board is arranged opposite to the steel bar. The extended section of the steel rod 2 exposed from the cathode carbon block 1 passes through the 80mm cathode paste layer 16, the 130mm anti-seepage casting material layer 17, the 65mm vermiculite insulation brick layer 18, and the 60mm xonotlite insulation brick layer 11 from the inside to the outside. The wrapping layer 9 of the extended section of the steel rod 2 corresponds to the cathode paste layer 16 and the anti-seepage casting material layer 17. The wrapping layer 9 can prevent moisture from entering the phosphorus pig iron layer and affecting the casting quality of the steel rod and the cathode carbon block.
[0049] The bottom pressure drop of the aluminum electrolytic cell using graphitized cathode carbon block group is significantly reduced, and the energy-saving effect is obvious; the graphitized cathode carbon block group has better resistance to sodium corrosion and can extend the service life of the cathode structure of the aluminum electrolytic cell; the performance of the graphitized cathode carbon block is uniform, and the probability of local early damage after being put into electrolytic operation is very small, which is conducive to the smooth operation of the overhaul cell; the graphitized cathode carbon block group has stable properties, and the cathode current distribution is more uniform after being put into electrolytic operation, which is conducive to the stable operation of the electrolytic cell.
[0050] The graphitized cathode carbon block has low resistivity (the resistivity at 1000°C is below 10μΩ·m) and high thermal conductivity (the thermal conductivity at 1000°C is above 50W / m·K). The steel rod is changed from a traditional double steel rod to a single steel rod, which increases the contact area between the steel rod and the cathode carbon block. Therefore, the heat generation at the steel rod is significantly reduced and the heat dissipation is greatly increased. The heat at the steel rod in the aluminum electrolytic cell can be dissipated to the outside through the steel rod extension section, and it is also convenient to cool the inner side of the aluminum electrolytic cell by cooling the steel rod extension section, thereby reducing the difference in thermal shrinkage between the graphitized cathode carbon block and the cathode paste, and eliminating or reducing the probability of cracks between carbon seams.
[0051] The above are only embodiments of the present invention. The invention is not limited to the field involved in this implementation case. The common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A graphitized cathode carbon block assembly, comprising a cathode carbon block and a steel rod, wherein the cathode carbon block is a graphitized carbon block, a steel rod paste layer is provided in the middle of the lower end surface of the cathode carbon block, grooves are provided at both ends of the lower end surface of the cathode carbon block, and the steel rods are provided in the grooves, characterized in that: A ceramic fiber blanket layer is provided between the steel rod and the steel rod paste layer, one end of the steel rod extends from the end of the cathode carbon block to the outside, a wrapping layer is provided on the extension section of the steel rod extending out of the cathode carbon block, the wrapping layer is made of a mixture of water glass and SiC ramming material, a phosphorus pig iron casting layer is provided between the steel rod and the inner side of the cathode carbon block, a ramming material layer is provided between the steel rod and the end of the cathode carbon block, the lower end of the steel rod extends downward from the lower end surface of the cathode carbon block, anti-seepage casting material layers are provided on both sides of the lower end of the steel rod, a plurality of anchors are symmetrically provided on both sides of the lower end of the steel rod, a plastic pipe is sleeved on the anchor, and the anchor is located in the anti-seepage casting material layer.
2. The graphitized cathode carbon block assembly according to claim 1, characterized in that: The weight ratio of water glass to SiC ramming material in the wrapping layer is 1-1.5:2-4, and the thickness of the wrapping layer is 0.5-1.5 mm.
3. The graphitized cathode carbon block assembly according to claim 1, characterized in that: The steel rod is a rectangular structure, and the width of the steel rod is greater than the thickness of the steel rod.
4. The graphitized cathode carbon block assembly according to claim 1, characterized in that: The thickness of the graphitized cathode carbon block group is above 480 mm.
5. A method for preparing a graphitized cathode carbon block assembly according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing the raw materials, calcining them at 1000-1200° C. for 10-15 hours, and after cooling, transferring them to a graphitization furnace for graphitization at 2500-2700° C. for 10-15 hours. After graphitization, forming them with a vibration forming machine, opening grooves, and obtaining a graphitized cathode carbon block; S2, sand wash the surface of the steel rod to remove rust from the steel rod, revealing a silver-grey metallic luster; S3, installing the steel rod into the groove of the cathode carbon block, heating the steel rod and the cathode carbon block, and quickly pouring the phosphorus pig iron molten liquid into the groove gap between the steel rod and the cathode carbon block to form a phosphorus pig iron pouring layer; S4. After the phosphorus pig iron casting is completed and cooled, the end of the cathode carbon block is filled with ramming material, and the three sides of the steel rod extension section are coated with a mixture of water glass and SiC ramming material to form a wrapping layer; S5. Anchors are welded on both sides of the steel rod, the anchors are wrapped with plastic tubes, and an anti-seepage castable is poured to form an anti-seepage castable layer; S6. A ceramic fiber blanket is arranged in the middle of the cathode carbon block near the steel rod, and the middle space is filled with paste to form a steel rod lake layer.
6. The preparation method according to claim 5, characterized in that: The raw materials of step S1 include electroforged anthracite, petroleum coke, asphalt, NbN additive and H3BO3 additive.
7. The preparation method according to claim 5, characterized in that: The anchor in step S6 is wrapped with a plastic tube having a thickness of 1.0 to 1.5 mm.
8. A graphitized cathode structure of an aluminum electrolytic cell using the graphitized cathode carbon block assembly according to any one of claims 1 to 4.
9. The graphitized cathode structure of an aluminum electrolytic cell using a graphitized cathode carbon block assembly according to claim 8, characterized in that: The graphitized cathode structure of the aluminum electrolytic cell comprises, from bottom to top, a cell shell, an insulation layer, an anti-seepage layer and a graphitized cathode carbon block group layer; the insulation layer comprises, from bottom to top, a brucite composite insulation brick layer, a xonotlite insulation brick layer, a high-strength ceramic fiber board layer and a ceramic vermiculite insulation board layer; the anti-seepage layer comprises, from bottom to top, a steel plate and a dry anti-seepage material layer; the graphitized cathode carbon block group layer comprises a plurality of graphitized cathode carbon block groups distributed in parallel, and the periphery of the graphitized cathode carbon block group layer comprises, from inside to outside, a cathode paste layer, an anti-seepage casting material layer, a vermiculite insulation brick layer and a xonotlite insulation brick layer.
10. The graphitized cathode structure of the aluminum electrolysis cell according to claim 9, characterized in that: The wrapping layer of the steel rod extension section corresponds to the cathode paste layer and the anti-seepage casting material layer.